2003
DOI: 10.1021/es034699v
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Variability in Pesticide and PCB Concentrations in Air near the Great Lakes

Abstract: Data through 2001 from the Integrated Atmospheric Deposition Network (IADN) were used to investigate the causes of variability in gas-phase polychlorinated biphenyl (PCB) and pesticide concentrations measured near Lakes Michigan, Erie, and Superior. A multiple linear regression model that incorporates temperature and time was used explain the variability in the concentrations. Our approach used autocorrelation analyses of the residuals to help us determine the effectiveness of the regression. Autocorrelation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 23 publications
6
53
0
Order By: Relevance
“…The calculated dates on which the pesticide concentrations in precipitation maximize at each of the IADN sites are listed in Tables S2-S8. Concentrations of endosulfan and γ-HCH, which are still in use, usually peaked in June or July, a time which corresponds well with their maximum agricultural usage (35,36). The use of all the other pesticides is restricted in the U.S., with the exception of methoxychlor, which is still being used in agriculture and on livestock.…”
Section: Resultsmentioning
confidence: 98%
“…The calculated dates on which the pesticide concentrations in precipitation maximize at each of the IADN sites are listed in Tables S2-S8. Concentrations of endosulfan and γ-HCH, which are still in use, usually peaked in June or July, a time which corresponds well with their maximum agricultural usage (35,36). The use of all the other pesticides is restricted in the U.S., with the exception of methoxychlor, which is still being used in agriculture and on livestock.…”
Section: Resultsmentioning
confidence: 98%
“…The variation of the estimated rates of decline for atmospheric components (dry and wet deposition, and vapor-phase concentration) was quite large with half-lives ranging from 6 to 20 years. It appears that the rate of decline decreased with the addition of more recent data (Buehler et al, 2004, Hillery et al, 1997, Hornbuckle et al, 2006, Schneider et al, 2001, Simcik et al, 1999. The purpose of the Scenario B and C forecasts was to provide boundaries for predicted long-term PCB water column concentrations by assuming a six-year and 20-year half-lives for PCB atmospheric components, respectively.…”
Section: Model Results and Discussionmentioning
confidence: 99%
“…Meijer et al (2001) found that the half-life time of p,p′-DDT in Luddington soils of the United Kingdom is 11.8 years, which is longer than those (8.2 ± 1.4 and 7.1 ± 1.0 years, respectively) in the atmosphere of Sleeping Bear Dunes and Sturgeon Points around the Great Lakes (Buehler et al, 2004). Hence, it is speculated that p,p′-DDT would degrade into p,p′-DDD faster in air than in soil, making soil a secondary source of p,p′-DDT and a sink of atmospheric p,p′-DDD.…”
Section: Tablementioning
confidence: 98%